Heinrich Mann's Small town tyrant - Fuchs, Dieter (Acta neophilologica, 2016)
This article considers the German Grammar School Novel from the first half of the twentieth century an all but forgotten Germanophone prototype of campus fiction. Whereas the Anglo-American campus novel of the 1970s, 80s and 90s features university professors as future-related agents of Western counterculture and free thought, the Grammar School Novel satirizes the German grammar school teacher known as Gymnasialprofessor as a representative of the past-related order of the autocratic German state apparatus from the beginning of the twentieth century. As Heinrich Mann's 1905 novel Professor Unrat / Small Town Tyrant (the source text of Marlene Dietrich's debut movie The Blue Angel) may be considered a foundational work of the German Grammar School Novel corpus, the main part of the article offers a sample analysis of this text.
Keywords: "Professor Unrat"; Anglo-American campus novel; German Grammar School Novel; German literature; German-language literature; gimnazijski roman; literarne študije; Mann, Heinrich, 1871-1950; Mann, Heinrich: Small Town Tyrant; Modri angel (film); nemška književnost; The Blue Angel (film)